ANALISIS KOMPARASI PERILAKU ETIS MAHASISWA AKUNTANSI STIE SAKTI ALAM KERINCI DENGAN STIE SUMATERA BARAT DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Sarmigi, Elex (Jurnal Benefita, 2018)
This study aims to see the comparison of ethical behavior of accounting students of STIE Sakti Alam Kerinci with accounting students of STIE Sumatera Barat. This study will also look at the comparative ethical behavior between male students and female students as well as the ethical behavior of individuals who have internal locus of control factors with individuals who have external locus of control factors separately from each college. In addition, this study will also look at the effects of equity sensitivity (X1) and culture (X2) on the ethical behavior of accounting students. This study uses primary data collected by using questionnaires. The method of testing the comparative hypothesis in this study is T-test, then multiple linear regression is used to analyze the influence of equity sensitivity (X1) and culture (X2) on ethical behavior (Y). This study found that (1) the accounting students of STIE Sumatera Barat have more ethical behavior than accounting students of STIE Sakti Alam Kerinci, (2) there are no differences of ethical behavior among male students and female students of STIE Sakti Alam Kerinci as well as STIE Sumatera Barat, (3a) The accounting students of STIE Sakti Alam Kerinci have internal locus of control factors has more ethical behavior than accounting student have external locus of control factors, (3b) there is no difference of ethical behavior among accounting students of STIE Sumatera Barat based on locus of control factors, (4a) Equity sensitivity and culture affect the ethical behavior of accounting students of STIE Sakti Alam Kerinci, (4b) equity sensitivity affects the ethical behavior of accounting students of STIE Sumatera Barat, but culture does not affect the ethical behavior of accounting students of STIE Sumatera Barat. Penelitian ini bertujuan untuk melihat komparasi perilaku etis mahasiswa akuntansi STIE Sakti Alam Kerinci dengan mahasiswa akuntansi STIE Sumatera Barat. Penelitian ini melihat komparasi perilaku etis antara mahasiswa dengan mahasiswi akuntansi serta perilaku etis individu yang memiliki faktor internal locus of control dengan individu yang memiliki faktor eksternal locus of control secara terpisah dari masing-masing perguruan tinggi. Selain itu, penelitian ini juga melihat pengaruh dari equity sensitivity (X1) dan budaya (X2) terhadap perilaku etis mahasiswa akuntansi. Penelitian ini menggunakan data primer yang dikumpulkan dengan menggunakan kuesioner. Metode pengujian hipotesis komparatif dalam penelitian ini adalah T-test, kemudian regresi linear berganda digunakan untuk menganalisa pengaruh equity sensitivity (X1) dan budaya (X2) terhadap perilaku etis (Y). Penelitian ini menemukan bahwa (1) mahasiswa akuntansi STIE Sumatera Barat memiliki perilaku yang lebih etis dibandingkan mahasiswa akuntansi STIE Sakti Alam Kerinci, (2) tidak terdapat perbedaan perilaku etis antara mahasiswa dan mahasiswi akuntansi STIE Sakti Alam Kerinci maupun STIE Sumatera Barat, (3a) mahasiswa akuntansi STIE Sakti Alam Kerinci yang memiliki faktor  internal locus of control memiliki perilaku lebih etis dibandingkan mahasiswa akuntansi yang memiliki faktor eksternal locus of control, (3b) tidak terdapat perbedaan perilaku etis antara mahasiswa akuntansi STIE Sumatera Barat berdasarkan faktor locus of control, (4a) equity sensitivity dan budaya mempengaruhi perilaku etis mahasiswa akuntansi STIE Sakti Alam Kerinci, (4b) equity sensitivity mempengaruhi perilaku etis mahasiswa akuntansi STIE Sumatera Barat